Exploring Primary Science Teachers' Creativity and Attitudes through Responses to Creative Questions in University Physics Lessons. - Nyet Moi Siew (2013)
To investigate the levels of primary science teachers’creativity through their responses in creativequestions carried out in university physics lessons;2.To find out the primary science teachers’creative attitudestowards the use ofcreative questionsin learning physics.Study design: Case study researchdesign.Place and Duration of Study: The study took place at the University of Malaysia Sabah for aperiod oftwohours.Methodology:The sample consisted of 74 in-service primary scienceteachers (age range 25-40 years) who tookMechanic, Matter and Heat as a core course towards Bachelor of Science Education.Simple creative questionswere infused into normal Physics lessons.The taskswerecontent-oriented, and the goalwasto yield a deeperunderstanding of whatwasbeing taught.The appropriate responses given to each creative question wereevaluated as to theirdivergent thinking:fluency, flexibility andoriginality (Torrance, 1974[32]).Questionnaireswith closed and open-ended questions wereadministeredto explore in what ways learners found their learningwith creative questions was different from ordinaryphysicslessons.Results:The results showed that a majority ofprimaryscienceteachersattained different levels of creativity whenassessed through creative questions-moderate level (65.8%), low level (31.5%) and only 2.7% were deemed tobe at an acceptable level.Results also revealed that creative questionsenable primary school teachers todevelop an increased level offluent and flexible thinking.Neverthelessthe originality dimensionof creative abilitiesofscience teacherswas at a low level.Conclusion:The primaryscienceteachers who participated in the study were mostly moderate creativeand onlya few of themweredeemed to becreative.This studyreveals thatphysicsknowledge is a necessary condition forcreativity development.The findingsof this studycouldimplythat either primary scienceteachersarenot so muchimpressed by theuse ofcreativequestioningas part of theirclassroomteachingpractice, or teachers havenotimplementedthe creativity elements of primarysciencecurriculum effectively, or both.Onthe whole, primaryschool teachers havepositive creative attitudes towards the use ofcreative questions in learning and teachingphysics